Full wolf moon ebook A novel. - Child, Lincoln (Jeremy Logan, 2017)
NEW YORK TIMES BESTSELLER • On the trail of a killer who cannot possibly exist ... Jeremy Logan, the renowned "enigmalogist," has often found himself in situations where keeping an open mind could mean the difference between life and death, and that has never been more true than now.      When Logan travels to an isolated writers' retreat deep in the Adirondacks to work on his book, he discovers the remote community has been rocked by the grisly death of a hiker on Desolation Mountain. The attack occurred during the full moon and the body was severely mauled, but the unusual savagery calls into question the initial suspicions of a bear attack. Logan's theories take a dramatic turn when he meets Laura Feverbridge, a respected scientist who is still struggling with the violent loss of her father months earlier. As Feverbridge shares her research with Logan, he begins to wonder whether he is actually up against something he can’t believe is real. Don't miss Lincoln Child's new thriller, Chrysalis !